2015
DOI: 10.1186/s13059-015-0815-x
|View full text |Cite
|
Sign up to set email alerts
|

The estrous cycle surpasses sex differences in regulating the transcriptome in the rat medial prefrontal cortex and reveals an underlying role of early growth response 1

Abstract: BackgroundMales and females differ in cognitive functions and emotional processing, which in part have been associated with baseline sex differences in gene expression in the medial prefrontal cortex. Nevertheless, a growing body of evidence suggests that sex differences in medial prefrontal cortex-dependent cognitive functions are attenuated by hormonal fluctuations within the menstrual cycle. Despite known genomic effects of ovarian hormones, the interaction of the estrous cycle with sex differences in gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 102 publications
6
41
0
Order By: Relevance
“…However, in other brain regions, the effect of the oestrous cycle can surpass sex differences. For example, Duclot and Kabbaj 52 have shown that the oestrous cycle surpasses sex differences in regulating the transcriptome of the rat medial prefrontal cortex. While hormonal replacement would elucidate whether oestrous cycle surpasses sex differences, or vice-versa, such an approach would entail stressful survival surgery and the stress of hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other brain regions, the effect of the oestrous cycle can surpass sex differences. For example, Duclot and Kabbaj 52 have shown that the oestrous cycle surpasses sex differences in regulating the transcriptome of the rat medial prefrontal cortex. While hormonal replacement would elucidate whether oestrous cycle surpasses sex differences, or vice-versa, such an approach would entail stressful survival surgery and the stress of hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the physiological variations of hormone levels occurring during the cycle represent a powerful tool to study the effects of sex hormones in many organs (i.e., the lung). By investigating females in a state of high or low levels of ovarian hormones related to the estrous cycle, researchers have demonstrated the existence of estrous cycle‐specific sex differences in tissues such as the brain and lung (Duclot and Kabbaj ; Fuentes et al. ; Fuentes and Silveyra ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, E2-induced Egr3 and Egr4 in OVX WT mice but not in OVX Het-Met mice. Members of the Egr family are involved in brain plasticity and neuropsychiatric disorders related to sex hormones [32,33]. Thus, it is likely that E2-related behavioral impairment is associated with a lack of plasticity in Het-Met mice in response to E2.…”
Section: Discussionmentioning
confidence: 99%